Greenman's principles of manual medicine - DeStefano, Lisa A.; Greenman, Ph. E., 1928- (Baltimore, MD : Lippincott Williams & Wilkins/Wollters Kluwer, 2011)
"This fully updated practical resource opens up one of the most enduring, yet continually evolving, areas of health care - manual medicine. With this informative, highly illustrated text, you'll learn the basic principles, specific techniques, and adjunct procedures of the discipline - including the use of exercise for prevention and treatment of common lower quarter neuromuscular syndromes."--BOOK JACKET
Structural diagnosis and manipulative medicine history -- Principles of structural diagnosis -- Barrier concepts in structural diagnosis -- The manipulative prescription -- Normal vertebral motion -- Concepts of vertebral motion dysfunction -- Principles of soft-tissue and other peripheral stimulating techniques -- Principles of muscle energy technique -- Mobilization with and without impulse technique -- Principles of indirect technique -- Principles of myofascial release and integrated neuromusculoskeletal technique -- Craniosacral technique -- Cervical spine technique -- Thoracic spine technique -- Rib cage technique -- Lumbar spine technique -- Pelvic girdle dysfunction -- Upper extremity technique -- Lower extremity technique -- Common clinical syndromes : exercise principles and prescriptions for the lower quarter -- Adjunctive diagnostic procedures -- Adjunctive therapeutic procedures
Rev. ed. of: Principles of manual medicine / Philip E. Greenman. 3rd ed. c2003
Includes bibliographical references and index
13
Keywords: Manipulation (Therapeutics); Manipulation, Orthopedic; Medicine, Physical; Physical and Rehabilitation Medicine; Physical medicine